2013
DOI: 10.1080/09670262.2013.860239
|View full text |Cite
|
Sign up to set email alerts
|

Molecular data show the enigmatic cave-dwelling diatomDiprora(Bacillariophyceae) to be a raphid diatom

Abstract: The diatom genus Diprora (Bacillariophyceae) was described from a cave on Kauaʻi, Hawaiʻi. Due to its lack of a raphe system and bilateral symmetry, the genus was first assigned to the Fragilariophycidae ('araphid diatoms'), but its systematic affinities were undetermined. We present a three-gene phylogeny, based on nuclear (SSU rDNA) and chloroplast (rbcL, psbC) genes, to determine the phylogenetic relationships of Diprora in the diatom tree of life. The concatenated multi-gene phylogenies, and the individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 49 publications
(45 reference statements)
1
20
0
Order By: Relevance
“…and Sellaphora species, in which Sellaphora would become paraphyletic if Eolimna is excluded from it (e.g. behnKe et al 2004;bruder & medlin 2008;mann & eVans 2007;eVans et al 2008;mann & sticKle 2009;rimet et al 2011;noVis et al 2012;KocioleK et al 2013;zGrundo et al 2013;KuliKoVsKiy et al 2014;Poulíčková et al 2015;zimmermann et al 2014.…”
Section: Final Remarks and Conclusionmentioning
confidence: 99%
“…and Sellaphora species, in which Sellaphora would become paraphyletic if Eolimna is excluded from it (e.g. behnKe et al 2004;bruder & medlin 2008;mann & eVans 2007;eVans et al 2008;mann & sticKle 2009;rimet et al 2011;noVis et al 2012;KocioleK et al 2013;zGrundo et al 2013;KuliKoVsKiy et al 2014;Poulíčková et al 2015;zimmermann et al 2014.…”
Section: Final Remarks and Conclusionmentioning
confidence: 99%
“…The genus Sellaphora is the most studied genus of the family from a molecular point of view, including the comprehensive work of D.G. Mann and coauthors (Mann et al 1999(Mann et al , 2003(Mann et al , 2004Evans et al 2008 (Kociolek et al 2013b;Kulikovskiy et al 2014a). These analyses indicated that two taxa are closely related and are part of one clade, but without any statistical support.…”
Section: Introductionmentioning
confidence: 99%
“…Cox (2015) has attempted to rectify this situation. Kociolek et al (2013b) studied enigmatic cavedwelling diatom Diprora Main from Hawaii. Due to its lack of a raphe system and bilateral symmetry, the genus was first assigned to the araphid diatoms (Main 2003), but its systematic affinities were undetermined.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the monotypic diatom genus Diprora Main was described as endemic from caves in Hawaii (MAIN 2003). This diatom has valves with typical pennate symmetry, but bears no hint of a raphe system at any stage during the ontogeny of the valve (KOCIOLEK et al 2013). Because of its symmetry and it lack of a raphe, Main suggested that it must be an 'araphid' diatom.…”
Section: What Does It Take To Describe a Genus? Some Traditional Respmentioning
confidence: 99%
“…A phylogenetic analysis of pennate diatoms using three genes (SSU rDNA, rbcL, psbC) showed Diprora haenaensis Main to be nested deep within the raphid pennate diatoms, being closely related to Sellaphora, Fallacia and Pinnularia (Fig. 2, see also KOCIOLEK et al 2013). Thus, while never exhibiting the feature of a raphe system, we would still assign this genus to the raphid diatoms.…”
Section: What Does It Take To Describe a Genus? Some Traditional Respmentioning
confidence: 99%